2014
DOI: 10.1051/0004-6361/201424659
|View full text |Cite
|
Sign up to set email alerts
|

General solution for the vacuum electromagnetic field in the surroundings of a rotating star

Abstract: Aims. Many recent observations of pulsars and magnetars can be interpreted in terms of neutron stars with multipole electromagnetic fields. As a first approximation, we investigate the multipole magnetic and electric fields in the environment of a rotating star when this environment is deprived of plasma. Methods. We compute a multipole expansion of the electromagnetic field in vacuum for a given magnetic field on the conducting surface of the rotating star. Then, we consider a few consequences of multipole fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…They found that the large density and pressure make the crust very strong and rigid, capable of supporting |ǫ| 4 × 10 −6 (assuming canonical neutron star mass and radius) before cracking suddenly in a collective manner (rather than yielding continuously). If we assume that the initial magnetic field does not deform the star sufficiently to crack the crust, then this limit translates to B (Young, Manchester, & Johnston 1999;Camilo et al 2000;Medin & Lai 2010), the anomalous braking index of some radio pulsars (Barsukov & Tsygan 2010), and the substructures found in some pulsar signals (Bonazzola, Mottez, & Heyvaerts 2015;Pétri 2015). While the dipole component of the magnetic field can be inferred from the observed spin-down rate, the putative higher-order multipoles contribute small corrections of order (2πνR * /c) 2 to the torque and cannot be measured directly.…”
Section: Axp 1e 2259+586 Anti-glitchmentioning
confidence: 99%
“…They found that the large density and pressure make the crust very strong and rigid, capable of supporting |ǫ| 4 × 10 −6 (assuming canonical neutron star mass and radius) before cracking suddenly in a collective manner (rather than yielding continuously). If we assume that the initial magnetic field does not deform the star sufficiently to crack the crust, then this limit translates to B (Young, Manchester, & Johnston 1999;Camilo et al 2000;Medin & Lai 2010), the anomalous braking index of some radio pulsars (Barsukov & Tsygan 2010), and the substructures found in some pulsar signals (Bonazzola, Mottez, & Heyvaerts 2015;Pétri 2015). While the dipole component of the magnetic field can be inferred from the observed spin-down rate, the putative higher-order multipoles contribute small corrections of order (2πνR * /c) 2 to the torque and cannot be measured directly.…”
Section: Axp 1e 2259+586 Anti-glitchmentioning
confidence: 99%
“…We suppose that there is the misalignment angle α between the rotational axis and the accretion column along magnetic axis so as to generate GW emission [43]. In the case of rigid rotation about a nonprincipal axis [18], the mass quadrupole moment can be represented as…”
Section: Accretion Columns and Gw Radiationmentioning
confidence: 99%
“…Therefore, the maximum amplitude of GW radiation produced from this mass quadrupole moment Q at a distance D of the source to the observer is given by [29,43]…”
Section: Accretion Columns and Gw Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, measurements of cyclotron resonant scattering lines [33] and pulse fractions in surface X-ray emissions [34] suggest that some neutron stars have local magnetic field strengths well in excess ( 3 orders of magnitude in some cases, such as 1E 1207.4-5209 [35]) of their spindown limits. Since magnetic stresses are known to induce mass density asymmetries within a star [36,37], magnetised neutron stars are therefore expected, in principle, to be excellent sources of continuous GWs [38,39]. In particular, these density asymmetries naturally lead to the generation of mass multipole moments, whose magnitude is proportional to the magnetic energy [20,40,41].…”
Section: Introductionmentioning
confidence: 99%